The use of ipsilateral and contralaterial recording of post-auricular muscle response in predicting hearing level - Abdullah, Rosninda (2015)
Ipsilateral and contralateral recording of tone burst evoked post-auricular muscle response (PAMR) were recorded in 55 adults (20 with normal hearing, 15 with conductive hearing loss and 20 with sensorineural hearing loss) to investigate the use of PAMR in predicting hearing level. In the first phase of this study, ipsilateral PAMR were elicited with three stimulus rates (6, 11 and 17/s) at several intensity levels (60, 40, 20 dB SL and at thresholds level) and at four octave frequencies (500, 1000, 2000 and 4000 Hz). In the second phase, thresholds level of ipsilateral and contralateral recordings of PAMR were recorded in normal, conductive and sensorineural hearing loss group. The findings of the first phase showed most of the PAMR were biphasic with the first peak latency of between 13.1 and 17.7 ms, while the second peak latency occurred between 16.7 and 22.2 ms, depending on the stimulus intensity, tone burst frequency, and post auricular muscle tone. There were no significant difference of PAMR peaks components (latency and amplitude) as the stimulus rates increased from 6 to 17/s (P>0.05), except at 500 Hz (P=0.03). The correlation analysis showed the best correlation value between PAMR and PTA thresholds at stimulus rate of 11/s (ICC=0.62-0.82) at frequency of 500, 1000 and 4000 Hz. In the second phase, the correlation between PAMR and PTA thresholds were the highest in SNHL group (ICC=0.81-0.93), followed by CHL group (ICC=0.77-0.94) and normal hearing group. Statistically, contralateral recording of PAMR showed lower thresholds than ipsilateral recording, particularly at higher frequencies. To conclude, the hearing thresholds obtained by PAMR were within 20 dB SL across the test frequencies with better estimates at the higher tone burst frequency (4 kHz) for both modes of stimulation (ipsilateral and contralateral). The findings of the current study demonstrate the ability of PAMR in predicting behavioural hearing levels among normal and hearing impaired adults.